Analysis of team success based on match technical and running performance in a professional soccer league - Andrzejewski, M.; Oliva-Lozano, J. M.; Chmura, P.; Chmura, J.; Czarniecki, S.; Kowalczuk, E.; Rokita, A.; Muyor, J. M.; Konefal, M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The aims of this study were to (1) determine the match technical and running performance required by different teams based on their final ranking position in a professional soccer league; and (2) analyze the correlation between teams` success at the end of the season and variables related to match technical and running performance.